Phenotyping for drought - Bioversity International (Bioversity International, 2015)
Water shortage is an important limiting abiotic factor in agriculture, and the problem is expected to increase with climate change causing more frequent and more severe droughts in many areas. Banana needs vast amounts of water for optimal production. In commercial Cavendish export production systems, irrigation is routinely used, which has reduced the sense of urgency to exploit genetic resources with drought tolerance traits. However, most banana production systems are small-scale rain-fed systems. In addition, banana production tends to move into drier climates to escape black leaf streak, economically the most threatening disease for banana production. There is a need to reduce the dependency on irrigation water to make banana production more sustainable.